2004
DOI: 10.1016/j.ccr.2004.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Distinct effects on gene expression of chemical and genetic manipulation of the cancer epigenome revealed by a multimodality approach

Abstract: We tested the hypothesis that the effects on gene expression of altered DNA methylation by 5-aza-2'-deoxycytidine (5-aza-CdR) and genetic (DNMT knockout) manipulation of DNA are similar, and distinct from Trichostatin A (TSA)-induced chromatin decondensation. Surprisingly, the effects of 5-aza-CdR were more similar to those of TSA than to DNMT1, DNMT3B, or double DNMT somatic cell knockout. Furthermore, the effects of 5-aza-CdR were similar at one and five days exposure, suggesting active demethylation or dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
144
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(161 citation statements)
references
References 39 publications
14
144
0
3
Order By: Relevance
“…Altered expressions of DNMTs have been linked to the cancer-associated hypermethylation of TSGs (Gius et al, 2004;Suzuki et al, 2004;Pruitt et al, 2005;Oka et al, 2006), as well as the hypomethylation of melanoma antigen gene MAGE-A1 (Loriot et al, 2006). We sought to determine which DNMT was involved in CSE-induced changes in the methylation pattern of SNCG.…”
Section: Cigarette Smoke Differentially Regulates Dnmts In A549 Cellsmentioning
confidence: 99%
“…Altered expressions of DNMTs have been linked to the cancer-associated hypermethylation of TSGs (Gius et al, 2004;Suzuki et al, 2004;Pruitt et al, 2005;Oka et al, 2006), as well as the hypomethylation of melanoma antigen gene MAGE-A1 (Loriot et al, 2006). We sought to determine which DNMT was involved in CSE-induced changes in the methylation pattern of SNCG.…”
Section: Cigarette Smoke Differentially Regulates Dnmts In A549 Cellsmentioning
confidence: 99%
“…Two chemical agents commonly used to modulate the expression of silenced genes in cancer cells are 5-aza-2 0 -deoxycytitdine (5-aza-dC), which is an inhibitor of DNA methylation and trichostatin A (TSA), an inhibitor of histone deacetylation (Marks et al, 2001;Johnstone, 2002;Yamashita et al, 2002). Gene expression studies revealed that the effects of 5-aza-dC are similar to those of TSA exposure than either of the somatic cell DNA methyltransferase knockouts (DNMT knockouts), implying a converging mechanism for these agents (Gius et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…51 Second, recent microarray analysis of human colon cancer cells (HCT116) revealed alterations in the gene expression profiles of 5-AzaC-treated cells irrespective of growth stage. 57 It also appears that among three DNMTs only DNMT1 is the target of 5-AzaC. Since gene expression profile of the inhibitor-treated HCT116 cells is similar to that of DNMT1 null cells, DNMT1 is likely to be the preferential target of 5-azaC.…”
Section: Reactivation Of Genes Silenced By Promoter Methylation: Epigmentioning
confidence: 99%
“…Since gene expression profile of the inhibitor-treated HCT116 cells is similar to that of DNMT1 null cells, DNMT1 is likely to be the preferential target of 5-azaC. 57 This observation is consistent with our earlier report that DNMT1 is selectively and rapidly degraded in animal cells following exposure to 5-azaC. 58 Recent study in our laboratory has shown that this selective degradation of DNMT1 is mediated by the proteasomal pathway (K Ghoshal and S Jacob, unpublished data), which offers an alternative mechanism of action for these potent anticancer drugs.…”
Section: Reactivation Of Genes Silenced By Promoter Methylation: Epigmentioning
confidence: 99%
See 1 more Smart Citation